The Development of Teaching Comics to Improve Interest in Reading Civic Education in MIN Ramba Padang, South Tapanuli Regency, Indonesia - Maulana Arafat Lubis (Budapest International Research and Critics University, 2018)
Indonesians seek information from social media more than books. Development of PPKn teaching materials in increasing reading interest MIN Ramba Padang in South Tapanuli district will focus on PPKn material such as joint decisions. The development of this teaching material is in the form of comics. The purpose of this study was to develop comic teaching materials to increase students' reading interest in PPKn subjects at MIN Ramba Padang kab Selatan Tapanuli Regency. This research method is research and development (R & D) method. This model is used to develop comics as teaching materials in high school SD / MI classes. While the subjects in this study were class V MIN Ramba Padang students who were located in Sipagimbar village, South Tapanuli regency as many as 17 people. The results of the study use the research method with ADDIE model.